On the necessity of separating investment and commercial banking - Adrian Blundell-Wignall (Intereconomics, 2011)
The fi nancial crisis has exposed all EU Member States - to different degrees - with a double economic policy challenge: to foster sustainable economic growth and to consolidate public finances. Can the governments in the EU afford to forego the benefi ts of targeted tax measures at EU level - tapping the growth potential of the internal market by reducing tax obstacles and improving tax collection on cross-border activities within the EU? This paper provides a short review of the varying tax structures in the EU Member States, discusses the interdependencies as well as the EU dimension of their tax policies and gives an overview on current and future tax initiatives at EU level.
Keywords: 330